2015
DOI: 10.1093/icesjms/fsv104
|View full text |Cite
|
Sign up to set email alerts
|

Natural swimming speed of Dascyllus reticulatus increases with water temperature

Abstract: Recent research on the relationship between coral reef water temperature and fish swimming activity has stated that swimming speed is inversely correlated with temperature above a species' optimum temperature (Johansen, J. L., and Jones, G. P. 2011. Increasing ocean temperature reduces the metabolic performance and swimming ability of coral reef damselfishes. Global Change Biology, 17: 2971–2979; Johansen, J. L., Messmer,V., Coker, D. J., Hoey, A. S., and Pratchett, M. S. 2014. Increasing ocean temperatures re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…In their analysis, a fish tank model, which allows to modify the temperature of the water [8], was used in contrast to our study which explores the data obtained from underwater videos in a natural setting that reflects the seasonal changes in water temperature. Some of our results have been reported previously in [7] from an ecological perspective where interested readers can find a deeper discussion regarding our findings and the findings of other studies. In [7], it was shown that one can still obtain statistically sound results, even with a dataset that contains examples of all the errors listed above.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In their analysis, a fish tank model, which allows to modify the temperature of the water [8], was used in contrast to our study which explores the data obtained from underwater videos in a natural setting that reflects the seasonal changes in water temperature. Some of our results have been reported previously in [7] from an ecological perspective where interested readers can find a deeper discussion regarding our findings and the findings of other studies. In [7], it was shown that one can still obtain statistically sound results, even with a dataset that contains examples of all the errors listed above.…”
Section: Introductionsupporting
confidence: 81%
“…Some of our results have been reported previously in [7] from an ecological perspective where interested readers can find a deeper discussion regarding our findings and the findings of other studies. In [7], it was shown that one can still obtain statistically sound results, even with a dataset that contains examples of all the errors listed above. It shows that by a combination of data binning and robust statistics over a large amount of data, statistically sound inferences can be made from the very noisy data (i.e.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The computer vision was first applied in monitoring fish swimming behavior with the purpose of observing the relationship between swimming and the climate specifically. Beyan C et al, obtained the continuous video frames through the computer vision to detect and track the changing speed of fish in different temperature, it is concluded that the relationship between climate and swimming [107]. Two previous studies [108][109][110] used cameras to detect Atlantic salmon swimming patterns to find that fish swimming speed not only varied with season and time of day but also is influenced by light intensity and feeding activity, too.…”
Section: Swimming Behaviourmentioning
confidence: 99%
“…Finally, given that water temperature influences both coral photosynthesis (e.g. Borell et al, 2008) and damselfish movement (Johansen and Jones, 2011;Beyan et al, 2015), the effects of rising water temperatures on the physiological aspects of fish-coral mutualisms are in need of further investigation. …”
Section: In Situ Recording Of Fish Behaviormentioning
confidence: 99%